Unipolar voltage threshold of 5.0 mV is optimal to localize critical isthmuses in post-infarction patients presenting with ventricular tachycardia. (6th May 2015) - Enriquez, Andres; Ali, Fariha Sadiq; Boles, Usama; Michael, Kevin; Simpson, Christopher; Abdollah, Hoshiar; Baranchuk, Adrian; Redfearn, Damian
Abstract: Introduction: Bipolar voltage mapping is useful to delineate post-infarct endocardial scar and guide ablation of ischemic VT. The role of unipolar mapping is not yet well defined. The aim of this study was to assess the correlation between electrophysiological findings in patients with ischemic VT and unipolar voltage maps using different cut-offs. Methods: We included 10 patients (age 67 ± 7 years, ejection fraction 33 ± 10%) with ischemic cardiomyopathy undergoing catheter ablation for recurrent VT. Patients with right-sided VTs were excluded. In all patients a unipolar voltage map was constructed during right ventricular pacing. Ablation was performed guided by activation and entrainment mapping in hemodynamically stable VTs and by pace-mapping and abnormal (late/split/fractionated) potentials in unstable VTs. Subsequently, the unipolar voltage maps were analyzed off-line using cutoffs from 1.0 to 8.0 mV and correlated with the isthmus sites. Results: A total of 17 sustained VTs were induced in the 10 patients and non-inducibility of the clinical VT was achieved in 90% of patients by endocardial ablation. The optimal cutoff was 5.0 mV. By using this value, the mean surface area of abnormal unipolar voltage was 43.8% and 95% of all VT isthmuses were located within the area of scar, as well as 81% of abnormal potentials. In addition, 71% of isthmuses were at less than 1 cm from the scar border. Conclusion: Unipolar voltage mapping showed good correlation with areas of isthmuses and abnormal electrograms in patients with scar-related VT, with a cut-off of 5.0 mV allowing the best delineation of ablation targets.